(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purpose of this study was to find out the effects of intensive interval training and extensive interval training on speed and cardio respiratory endurance. To realize the objective of the present study 45 male students in the age group of 18-24 years, studying at Annamalai University’s Department of physical education were randomly selected as subjects. The selected subjects were divided into three groups of fifteen each. Group I was subjected intensive interval training, group II was subjected to extensive interval training and the group III was the control group. The intensive interval training group and extensive interval training group underwent their respective trainings for three days per week for twelve weeks in which the control group did not participate any special training program apart from their regular physical education as pre required by their curriculum. Speed and cardio respiratory endurance were considered as criterion variable for the present study. The necessary data were collected by subjecting all the individuals to the tests on selected dependent variables both pre and post training period. The analysis of covariance was used to analyze the significant difference, if any among the groups. Since, three groups were compared, whenever the obtained ‘F’ ratio for adjusted posttest was found to be significant, the Scheffe’s test to find out the paired mean differences, if any. The .05 level of confidence was fixed as the level of significance to test the ‘F’ ratio obtained by the analysis of covariance, which was considered as an appropriate. The results of the study showed that there was a significant difference among intensive interval training group extensive interval training group and control group on speed and cardio respiratory endurance.